Mongolian development bank - Tulga, Zorigsaikhan (KDI School, 2011)
First of all I would like to convey my deepest gratitude to my supervisors Nam San-Woo and Cho Yoon-Cheong whose heart fully supported me to accomplish this project by giving me lot’s of their precious time. When I had difficulties, my professors fully understood and helped me from the beginning to the end. I also thank all of the KDI staff, who gave me motivation to finish my thesis. By doing this project, I have gained tremendous knowledge. I am grateful that I had a chance to come here at KDI, the great hall of knowledge and became to know knowledgeable and intellectual professors.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Mongolian